2020
DOI: 10.3390/w12113141
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Lime-Treated Lateritic Soil for Reservoir Shoreline Stabilization

Abstract: Sedimentation is one of the major problems addressed by reservoir management, and requires extensive effort to control it. This paper aims to evaluate the efficiency of the soil–lime stabilization technique for reservoir shores. The treatment consisted of spraying hydrated lime in slurry form over the surface of a lateritic clay sample with 1, 2, and 4% lime solution and curing times of 1, 7, 28, and 56 days with air-drying and moist-room storage. In addition, a single test with less than 1% lime solution by w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
2
0
0
Order By: Relevance
“…Figure 15 shows SEM images of the raw granular lateritic soil, hydrate lime, and ZL-2A stabilizer. Quartz and kaolinite were observed in the lateritic soil, which is consistent with previous research [41], and numerous calcium crystals were observed in the lime sample. The dehydrated ZL-2A stabilizer resembled a pile ball and had numerous cilia on its surface, which is a mixture of high-molecular-weight organic matter and inorganic matter such as sodium hydroxide.…”
Section: Sem Image Characterizationsupporting
confidence: 92%
See 1 more Smart Citation
“…Figure 15 shows SEM images of the raw granular lateritic soil, hydrate lime, and ZL-2A stabilizer. Quartz and kaolinite were observed in the lateritic soil, which is consistent with previous research [41], and numerous calcium crystals were observed in the lime sample. The dehydrated ZL-2A stabilizer resembled a pile ball and had numerous cilia on its surface, which is a mixture of high-molecular-weight organic matter and inorganic matter such as sodium hydroxide.…”
Section: Sem Image Characterizationsupporting
confidence: 92%
“…Figure 15 shows SEM images of the raw granular lateritic soil, hydrate lime, and ZL-2A stabilizer. Quartz and kaolinite were observed in the lateritic soil, which is consistent with previous research [41], and numerous calcium crystals were observed in the lime…”
Section: Sem Image Characterizationsupporting
confidence: 92%